Mobilization and Cellular Distribution of Phosphate in the Diatom Phaeodactylum tricornutum - Dell’Aquila, Gianluca; Zauner, Stefan; Heimerl, Thomas; Kahnt, Jörg; Samel-Gondesen, Vera; Runge, Simon; Hempel, Franziska; Maier, Uwe G. (Frontiers in Plant Science, 2020)
Unicellular organisms that live in marine environments must cope with considerable fluctuations in the availability of inorganic phosphate (Pi). Here, we investigated the extracellular Pi concentration-dependent expression, as well as the intra- or extracellular localization, of phosphatases and phosphate transporters of the diatom Phaeodactylum tricornutum. We identified Pi-regulated plasma membrane-localized, ER-localized, and secreted phosphatases, in addition to plasma membrane-localized, vacuolar membrane-localized, and plastid-surrounding membrane-localized phosphate transporters that were also regulated in a Pi concentration-dependent manner. These studies not only add further knowledge to already existing transcriptomic data, but also highlight the capacity of the diatom to distribute Pi intracellularly and to mobilize Pi from extra- and intracellular resources.